Cognitive training and Bacopa monnieri: Evidence for a combined intervention to alleviate age associated cognitive decline. (October 2016) - McPhee, Grace M.; Downey, Luke A.; Noble, Anthony; Stough, Con
Abstract: As the elderly population grows the impact of age associated cognitive decline as well as neurodegenerative diseases such as Alzheimer's disease and dementia will increase. Ageing is associated with consistent impairments in cognitive processes (e.g., processing speed, memory, executive function and learning) important for work, well-being, life satisfaction and overall participation in society. Recently, there has been increased effort to conduct research examining methods to improve cognitive function in older citizens. Cognitive training has been shown to improve performance in some cognitive domains; including memory, processing speed, executive function and attention in older adults. These cognitive changes are thought to be related to improvements in brain connectivity and neural circuitry. Bacopa monnieri has also been shown to improve specific domains of cognition, sensitive to age associated cognitive decline (particularly processing speed and memory). These Bacopa monnieri dependent improvements may be due to the increase in specific neuro-molecular mechanisms implicated in the enhancement of neural connections in the brain (i.e. synaptogenesis). In particular, a number of animal studies have shown Bacopa monnieri consumption upregulates calcium dependent kinases in the synapse and post-synaptic cell, crucial for strengthening and growing connections between neurons. These effects have been shown to occur in areas important for cognitive processes, such as the hippocampus. As Bacopa monnieri has shown neuro-molecular mechanisms that encourage synaptogenesis, while cognitive training enhances brain connectivity, Bacopa monnieri supplementation could theoretically enhance and strengthen synaptic changes acquired through cognitive training. Therefore, the current paper hypothesises that the combination of these two interventions could improve cognitive outcomes, over and above the effects of administrating these interventions independently, as an effective treatment to ameliorate age associated cognitive decline.